2022
DOI: 10.3390/genes13020258
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TRPM4 Gene Mutations in Causing Familial Progressive Cardiac Conduction Disease: A Further Contribution

Abstract: Progressive cardiac conduction disease (PCCD) is a relatively common condition in young and elderly populations, related to rare mutations in several genes, including SCN5A, SCN1B, LMNA and GJA5, TRPM4. Familial cases have also been reported. We describe a family with a large number of individuals necessitating pacemaker implantation, likely due to varying degrees of PCCD. The proband is a 47-year-old-patient, whose younger brother died at 25 years of unexplained sudden cardiac death. Three paternal uncles nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…TRPM4 heterozygous mutations are linked to isolated cardiac conduction disorders and progressive familial heart block type I. 11 RANGRF codes for Ran Guanin Nucleotide Release Factor and regulates the expression and function of the Nav1.5 cardiac sodium channel in humans. 12 RANGRF mutations were related to BS and histiocytoid cardiomyopathy in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPM4 heterozygous mutations are linked to isolated cardiac conduction disorders and progressive familial heart block type I. 11 RANGRF codes for Ran Guanin Nucleotide Release Factor and regulates the expression and function of the Nav1.5 cardiac sodium channel in humans. 12 RANGRF mutations were related to BS and histiocytoid cardiomyopathy in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…TRPM4 is expressed predominantly in cardiac and smooth muscle cells. TRPM4 heterozygous mutations are linked to isolated cardiac conduction disorders and progressive familial heart block type I 11 . RANGRF codes for Ran Guanin Nucleotide Release Factor and regulates the expression and function of the Nav1.5 cardiac sodium channel in humans 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported a strong link between TRPM4 genetic variants and cardiac conduction disorders (Kecskes et al, 2015 ; Liu et al, 2013 ; Palladino et al, 2022 ; Stallmeyer et al, 2012 ). Experimental studies have revealed similar findings in mouse models (Demion et al, 2014 ; Guinamard et al, 2006 ; Liu et al, 2010 ; Mathar et al, 2010 , 2014 ; Pironet et al, 2019 ) using different Trpm4 −/− mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported a strong link between TRPM4 genetic variants and cardiac conduction disorders (Kecskes et al 2015, Liu, Chatel, Simard, Syam, Salle, Probst, Morel, Millat, Lopez, Abriel, Schott, Guinamard and Bouvagnet 2013, Palladino et al 2022, Stallmeyer, Zumhagen, Denjoy, Duthoit, Hebert, Ferrer, Maugenre, Schmitz, Kirchhefer, Schulze-Bahr and Guicheney 2012). Experimental studies have revealed similar findings in mouse models (Demion, Thireau, Gueffier, Finan, Khoueiry, Cassan, Serafini, Aimond, Granier, Pasquie, Launay and Richard 2014, Guinamard et al 2006, Liu, El Zein, Kruse, Guinamard, Beckmann, Bozio, Kurtbay, Megarbane, Ohmert, Blaysat, Villain, Pongs and Bouvagnet 2010, Mathar et al 2014, Mathar, Vennekens, Meissner, Kees, Van der Mieren, Camacho Londono, Uhl, Voets, Hummel, van den Bergh, Herijgers, Nilius, Flockerzi, Schweda and Freichel 2010, Pironet et al 2019).…”
Section: Discussionmentioning
confidence: 99%